Digital Organizational Culture: Concept and Scale Development - Lukito, Daniel; Suharnomo, Suharnomo; Perdhana, Mirwan S.; Jayanti, Sanni Tri (Journal The Winners, 2025)
This research presented a multifaceted conceptualization of digital organizational culture (DOC) to address challenges from a divergent understanding of critical concept among strategic decision-makers. In this context, the existing definition of DOC remained fragmented and insufficient, despite numerous analyses emphasizing the significance of DOC in digital transformation. A new theoretical concept of DOC was developed using grounded theory, considering the evidence from an extensive literature review and synthesis. Data were collected from 345 founders or C-level executives of Indonesian manufacturing organizations with at least 100 employees. The coding analysis results show DOC as a higher order construct with four dimensions namely sensitive, competitive, united, and dynamic. The construct was used as the foundation in developing the conceptual definition of DOC. DOC scale was then developed to transform the DOC into a more practical variable. The results show that the formulation of a thorough conceptual definition of DOC introduced and validated a measurement scale for assessing the concept. While testing the nomological validity of the scale, this study also proves the relation among DOC and change leadership, and project effectiveness. Practitioners may benefit from the results, offering constructive awareness by clarifying the nature of DOC and opening new opportunities for further investigation and application.